Paraguay : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2002 Article IV Consultation highlights that Paraguay's economic performance in recent years has been characterized by slow economic growth and increasing unemployment and poverty rates. This stagnation reflects structural impediments to growth, exacerbated by external and domestic shocks. In 2002, the economy fell into its worst recession in decades, with real GDP down by 2 1\2 percent, according to official estimates, or 4 1\2 percent, according to IMF staff estimates, while inflation accelerated to 14 1\2 percent. The public finances also deteriorated sharply in 2002.